2012
DOI: 10.1186/1750-1326-7-35
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic influence of phosphorylation and metal ions on tau oligomer formation and coaggregation with α-synuclein at the single molecule level

Abstract: BackgroundFibrillar amyloid-like deposits and co-deposits of tau and α-synuclein are found in several common neurodegenerative diseases. Recent evidence indicates that small oligomers are the most relevant toxic aggregate species. While tau fibril formation is well-characterized, factors influencing tau oligomerization and molecular interactions of tau and α-synuclein are not well understood.ResultsWe used a novel approach applying confocal single-particle fluorescence to investigate the influence of tau phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 61 publications
7
58
0
1
Order By: Relevance
“…High concentrations of iron can increase oxidative stress and the toxicity of environmental or endogenous toxins, causing diseases such as AD and Parkinson's disease. At this stage, the oxidative injury and iron accumulation caused by HO-1 promote tauopathies, as previously reported [53,74,75].…”
Section: Discussionmentioning
confidence: 59%
“…High concentrations of iron can increase oxidative stress and the toxicity of environmental or endogenous toxins, causing diseases such as AD and Parkinson's disease. At this stage, the oxidative injury and iron accumulation caused by HO-1 promote tauopathies, as previously reported [53,74,75].…”
Section: Discussionmentioning
confidence: 59%
“…The oligomeric intermediates or amyloid forms of many proteins that are linked to human diseases demonstrate SDS resistance, including A␤ peptide, Tau, mammalian prion protein PrP, and proteins with polyglutamine stretches (55)(56)(57). Other functional amyloid proteins and yeast prion proteins also share this property (16, 58 -60).…”
Section: Discussionmentioning
confidence: 99%
“…Using the fluorescent intensity distribution analysis technique (FIDA), Nübling and colleagues have shown that tau and αsyn can form co-oligomers and that co-aggregation happens even at nanomolar concentrations but only in the presence of a cationic aggregation inducer such as Al 3+ and Fe 3+ or DMSO [158]. Moreover, tau phosphorylation by GSK3β strongly enhanced the formation of mixed oligomers [158].…”
Section: Tau and α-Synuclein In Molecular Studiesmentioning
confidence: 99%